(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the article there are analyzed philosophical aspects of the concept of consent and the idea of dialogue. Dialogue and consent are social and philosophical problems and cover many areas of society. At the same time they are ambiguouson their functional role. These ideas focused on civilized solution of any contradictions and are reliable, proven tools of overcoming socially hazardous conflicts. Key words: consent, dialogue, spiritual values, culture, mutual understanding, interethnic consent, tolerance.